"Jefferson said that my hair is ugly and bad": curly hair and empowerment of black girls in child day care - Rosa Silvia Lopes Chaves; Waldete Tristão de Oliveira (Universidade Federal de Santa Catarina, 2018)
This article discusses the empowerment of black children's identities from the deconstruction of beauty stereotypes around curly hair, black skin, and childhood cultures, in the context of a government day care facility in the city of São Paulo, Brazil. The research highlights how the manners of touching, grooming, combing, and styling the children's hair carry strong messages for the black girls, who seek, in these relationships with teachers and with other children, elements for a positive construction of their identities. Sociology of Childhood is our reference to investigate the children's point of view, perceiving them as social actors, who are historical agents and culture producers. Racial and gender roles serve as categories for analyzing the collected data. The results reaffirm the importance of investigations that address the complex, intricate relationships between gender, race, and childhood in day care centers.